Socio-economic Problems Faced by Male Elderly Persons in Pashtun Society (A case study of Umarzai Charsadda) - Tanveer Alam; Rohul Amin; Sayed Muhammad Shabab, (Dialogue Social Science Review (DSSR), 2025)
Aging is a natural phenomenon. The increasing aging population is emerging challenge for both developing and under develop countries. Population ageing regarded as one of the most critical challenge of developed societies. Every phase of life has different problems. Pakistan older population, which has reached already 12.5 million, will double by 2030 and will reach to close 40 million by 2050. In pakhtun society, male elderly person respected recognized important part of the family. However, with time humans become weak lose their status become dependent socially and financially on family members in society. The the last phase of life arise different challenges to the aging population. There are so many challenges are exist in Pashtun society for older people. This research paper focused on socio-economic problems faced by male elderly in Pashtun society a study of Umarzai charsadda. It is quantitative in nature total sample size was 40 population above from age 60 male elderly people in Umarzai charsadda. Using non-probability convenience sampling data was collected with the help of structured interview questions. Data analyzed by the Statistical Package for Social Sciences (SPSS). The findings revealed that the majority of male elderly persons were illiterate dependent on family unsatisfied with their current income, poverty ratio has high in Umarzai, on the other hand male elderly financially supporting their sons, most male elderly has two earning members in family, decrease mobility limited social participation in society, and poverty ratio is high. This research underscores the importance of older people are treasure for the young peoples and government and non-government organization highlight the issues of the elderly persons in Khyber Pakhtunkhwa, resolve their pension issues.